Targeting T Cell Metabolism for Tumor Therapy: A Review - Cinthya Karlina Wijaya; Febriana Catur Iswanti (Indonesian Journal of Cancer, 2026)
Background: Immunometabolism explores the connection between metabolism and the immune system. T cells require nutrients like glucose, lipids, and amino acids for proper function, but tumors compete for these resources and create a suppressive microenvironment that weakens T cell activity. This article examines how T cell metabolism affects antitumor immunity and whether targeting metabolic pathways can improve cancer treatment. Methods: A narrative review was conducted by searching databases like PubMed, Scopus, and Google Scholar using keywords such as "T cell metabolism AND cancer immunotherapy." The review focused on high-impact journals and included peer-reviewed articles, review papers, and experimental studies published in the last 10 years. Excluded studies were non-peer-reviewed, outdated, or unrelated to T cell metabolism in cancer. Key data were extracted, categorized into themes like metabolic pathways, immunosuppressive mechanisms, and therapeutic strategies, and critically analyzed. Results: The review highlights the essential role of T cell metabolism in antitumor immunity. Tumors create a nutrient-deprived environment that inhibits T cell function, competing for nutrients like glucose, lipids, and amino acids. Additionally, tumors express checkpoint receptors and immunosuppressive molecules that further reduce T cell activity. Recent research focusing on metabolic reprogramming to enhance T cell resilience, with strategies like boosting glycolysis, optimizing lipid metabolism, and targeting regulators like mTOR, shows promise. Combining these metabolic interventions with existing immunotherapies, such as checkpoint inhibitors, is gaining attention.Conclusions: The review emphasizes the importance of T cell metabolism in overcoming tumor-induced immunosuppression. Metabolic reprogramming, especially enhancing glycolysis and targeting metabolic regulators, can improve T cell activity and antitumor responses. Combining these strategies with immunotherapies offers promising potential, though further research is needed to refine approaches and address clinical challenges.